1987
DOI: 10.1007/bf01402365
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation disorders following acute head injury

Abstract: Coagulation disorders following acute head injury were investigated in 100 patients: 81 patients survived and 19 patients died. Disseminated intravascular coagulation (DIC) was seen in 24%, and occurred most frequently in acute subdural haematoma, followed by contusional haematoma and contusion. Mortality rate of the patients with DIC was 58%. Level of serum fibrin-fibrinogen degradation product (FDP) was correlated with the amount of damaged tissue. The factors which influenced the prognosis for life were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 22 publications
2
16
0
1
Order By: Relevance
“…These results are consistent with those from other studies conducted among adults, which have shown that low fibrinogen levels, elevated FDP, low platelet counts and delayed aPTT are predictors of a low GOS [5, 17]. In fact, the significant association between the changes in aPTT and FDP, and the outcome of patients with head injury, suggests that these hemocoagulative measures are good predictors of outcome [26, 27, 28]. We found a statistically significant association between aPTT, FDP and the outcome of the traumatized children, and the extent of statistical significance increased with the variation of these parameters.…”
Section: Discussionsupporting
confidence: 82%
“…These results are consistent with those from other studies conducted among adults, which have shown that low fibrinogen levels, elevated FDP, low platelet counts and delayed aPTT are predictors of a low GOS [5, 17]. In fact, the significant association between the changes in aPTT and FDP, and the outcome of patients with head injury, suggests that these hemocoagulative measures are good predictors of outcome [26, 27, 28]. We found a statistically significant association between aPTT, FDP and the outcome of the traumatized children, and the extent of statistical significance increased with the variation of these parameters.…”
Section: Discussionsupporting
confidence: 82%
“…There are variable data in the literature and different studies associated one or more of the following with TBI progression: Prothrombin time (PT) or INR, Partial thromboplastin time (PTT), thrombocytopenia, high fibrin degradation and low fibrinogen levels. [25][26][27][28][29][30] Fewer other studies reported no association between coagulopathy and bleeding progression in TBI. [31][32][33] This considerable variation is attributed to lack of consensus on TBI-coagulopathy definition, heterogeneity of patients involved, variable laboratory tests used in different studies and timing to perform these tests and CTs.…”
Section: Coagulopathy and Edhpmentioning
confidence: 98%
“…Recently, acute posttraumatic coagulopathy has been recognized as another major complication contributing to secondary brain injury and impaired outcome after TBI [3][4][5][6][7][8][9][10][11][12][13], but detailed information on its frequency and potential risk factors to aggravate the detrimental effects of this coagulopathy is still lacking. This retrospective analysis was conducted to assess the overall frequency of acute post-traumatic coagulopathy in patients with isolated blunt TBI, to evaluate its potential effects on outcome and to determine risk factors contributing to acute TBI-associated coagulopathy, all by using a large multi-center population-based trauma registry.…”
Section: Introductionmentioning
confidence: 99%